Bidirectional detection method using for hall effects sensors for water flow measurement system - Garmabdari, Rasoul (2014)
Natural resources are defined as material and components which are derived naturally from environment and they exist in a natural form and undisturbed by humanity. According to the statistical investigations, during the last century, the water consumption has grown two times more than the growth rate of population. Based on these studies, this amount of water is used for different purposes including 70% for agriculture, 20% for industry and 10% for domestic usage. The water management is taken into account as one of the natural resources, which must be managed and it can be achieved by measurement and monitoring the water consumption and water flow, which are considered as crucial issues in industry and domestic usages. Numerous water flow measurement (WFM) systems have been reported such as Hall-Effect (HE) sensor based WFM systems, which also can be categorized into different types such as single HE sensor, two HE sensors and three HE sensors based WFM systems. However, there are some weaknesses in their measurement techniques such as capability to detect the flow direction, high sensitivity against noise and disturbances signals, low accuracy, and high power consumption. Furthermore, none of them are capable of recognizing the source of occurred error, which makes troubleshooting of these systems a time consuming task, due to necessity to disassemble the system. The design of the proposed four HE sensors based WFM system can be separated into three main units, including motion sensing unit (MSU), data acquisition and processor unit (DAPU), and measurement and monitoring unit (MMU). The MSU is based on four analog HE sensors and two permanent magnets, which are differentially arranged on rotating disc and fixed plate. This arrangement generates 8 sequential codes that can determine the flow direction and it increases the accuracy of WFM system as well. The DAPU consists of four differential amplifiers, schmittriggers, and voltage level shifters. The configuration of MSU and DAPU is purposely designed to reduce the effects of noise and disturbance signals. Lastly, a measurement and monitoring algorithm is developed based on Labview to calculate the flow rate, water consumption and detect the error source and flow direction. Although, in this research, an artificial turbine is used instead of actual turbine, but their operation principles are similar. A proposed WFM system based on four HE sensors has been designed and implemented. The functionality and performances of the system has been confirmed. The results indicated that the proposed four HE sensors based WFM system is able to measure the water flow rate in both forward and reverse flow direction between 0 to 52 liter/minute and water consumption. Additionally, the flow direction and the error source can be determined based on generated sequential code. Moreover, the noise analysis was performed and the spectral noise density of the designed WFM system was resulted almost 35 nV between 0 to 9 kHz, therefore, the immunity of proposed WFM system against disturbance signal and noise, is confirmed. The power consumption is also reduced by using switch technique by 95.68% as compared with conventional WFM systems. The developed WFM system can be applied in other applications such as oil and gas meters, wind turbine, RPM meter of automobile, automatic meter reading (AMR) systems and any rotary movement based apparatuses.